A (FeCoNiCuZn)F high entropy fluoride electrocatalyst and preparation method thereof

By depositing FeCoNiCuZn metal ions using foam nickel matrix and constant potential electrodeposition method in the electrolytic water system, and fluorinating the (FeCoNiCuZn)F high-entropy fluoride electrocatalyst is prepared, which solves the problem of scarce resources and high cost of precious metal electrocatalysts, and achieves low-cost and efficient electrocatalytic performance.

CN115961305BActive Publication Date: 2025-04-18NORTHEASTERN UNIV AT QINHUANGDAO
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310047413.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-31
Publication Date
2025-04-18
Estimated Expiration
2043-01-31

AI Technical Summary

Technical Problem

Precious metal electrocatalysts are needed in existing electrolytic systems, and their resources are scarce and costly, limiting their large-scale application.

Method used

Using foam nickel as the matrix, five metal ions of FeCoNiCuZn were uniformly deposited by constant potential electrodeposition method, and then fluorinated by molten salt method to prepare (FeCoNiCuZn)F high entropy fluoride electrocatalyst.

Benefits of technology

It has achieved a low-cost and excellent performance transition metal-based electrocatalyst, with excellent dual-function electrocatalytic performance of hydrogen evolution and oxygen evolution, and is suitable for large-scale applications of electrolytic water systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115961305B_ABST
    Figure CN115961305B_ABST
Patent Text Reader

Abstract

A (FeCoNiCuZn)F high entropy fluoride electrocatalyst and a preparation method thereof, belonging to the field of catalyst material preparation. The (FeCoNiCuZn)F high entropy fluoride electrocatalyst uses a precursor solution with a molar ratio of metal ions of Fe 3+ :Co 2+ :Ni 2+ :Cu 2+ :Zn 2+ =1:1:1:1:1, according to 10cm 3 The corresponding molar amount of the fluorine-containing compound added to the FeCoNiCuZn high entropy alloy is 0.054-0.067 mol. The preparation method is as follows: a precursor solution is prepared according to the molar ratio of metal ions, and electrodeposition is performed to form a FeCoNiCuZn high entropy alloy on a porous conductive nickel foam substrate, and the alloy is fluorinated to form a (FeCoNiCuZn)F high entropy fluoride electrocatalyst. The preparation method is simple to operate, low in preparation cost, fast in preparation time, and the obtained electrocatalyst has a stable structure and excellent dual-functional electrocatalytic performance of hydrogen and oxygen evolution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalyst material preparation, and specifically relates to a (FeCoNiCuZn)F high entropy fluoride electrocatalyst and a preparation method thereof. Background Art

[0002] The electrolytic water system consists of two half reactions: the cathode hydrogen evolution reaction and the anode oxygen evolution reaction. Given the slow reaction kinetics, precious metal electrocatalysts (Pt, IrO2, RuO2) are required to improve the conversion efficiency between electrical energy and chemical energy. However, the scarce and expensive reserves of precious metal resources limit their large-scale application in electrolytic water systems. Therefore, the development of transition metal-based electrocatalysts with high efficiency, stability and low cost is the key to promoting the large-scale application of electrolytic water, and it is also a difficult problem that urgently needs to be overcome.

[0003] High-entropy material catalysts containing multiple metal components have excellent electrocatalytic efficiency due to the synergistic effect of multiple elements. High-entropy anion compound electrocatalysts have attracted extensive attention in the field of electrocatalysis due to their high conductivity, stable structure, and excellent performance. Currently reported high-entropy anion compound electrocatalysts mainly include high-entropy oxides, high-entropy sulfides, high-entropy phosphides, etc., but there are few processes that can achieve simple preparation methods, high catalytic activity, and practical large-scale preparation of high-entropy anion compound electrocatalysts. It is particularly important to develop new components of high-entropy anion compound electrocatalysts and preparation process flows. Summary of the invention

[0004] The present invention aims at the urgent need of the prior art and provides a (FeCoNiCuZn)F high entropy fluoride electrocatalyst and a preparation method and application thereof. The preparation method is easy to operate, has low preparation cost and fast preparation time. The prepared (FeCoNiCuZn)F high entropy fluoride electrocatalyst not only has great scientific research significance, but also is conducive to large-scale batch actual production and has certain economic value potential.

[0005] The preparation method of the present invention uses nickel foam as a substrate, utilizes a constant potential electrodeposition method to uniformly reduce and deposit five metal ions on the substrate, and then performs a simple molten salt fluorination treatment to obtain a (FeCoNiCuZn)F high entropy fluoride electrocatalyst.

[0006] The equipment of the invention is easy to obtain and the operation process is simple. The prepared (FeCoNiCuZn)F high entropy fluoride electrocatalyst has a stable structure and has relatively excellent dual-functional electrocatalytic performance of hydrogen evolution and oxygen evolution.

[0007] The (FeCoNiCuZn)F high entropy fluoride electrocatalyst of the present invention uses a precursor solution with a metal ion molar ratio of Fe 3+ :Co2+ :Ni 2+ :Cu 2+ :Zn 2+ =1:1:1:1:1, the amount of fluorine-containing compound is determined according to the area of ​​the FeCoNiCuZn high entropy alloy. Preferably, 10 cm 3 The corresponding molar amount of the fluorine-containing compound added to the FeCoNiCuZn high entropy alloy is 0.054-0.067 mol;

[0008] Furthermore, the fluorine-containing compound is preferably ammonium fluoride.

[0009] The structure of the (FeCoNiCuZn)F high entropy fluoride electrocatalyst is a cubic crystal system with a space group of Fm-3m. Under 1 mol / L KOH alkaline conditions, the hydrogen evolution reaction of the (FeCoNiCuZn)F high entropy fluoride electrocatalyst was measured at a current density of 10 mA·cm -2 The overpotential is 21 mV and the Tafel slope is 24.57 mV·dec -1 ; The current density of oxygen evolution reaction was measured at 100 mA cm -2 The overpotential is 274 mV and the Tafel slope is 48.86 mV·dec -1 , and has excellent electrocatalytic performance in hydrogen evolution reaction and oxygen evolution reaction.

[0010] The invention discloses a method for preparing a (FeCoNiCuZn)F high entropy fluoride electrocatalyst, wherein the molar ratio of metal ions is Fe 3+ :Co 2+ :Ni 2+ :Cu 2+ :Zn 2+ =1:1:1:1:1 prepare a precursor solution, carry out electrodeposition, form a FeCoNiCuZn high entropy alloy on a porous conductive nickel foam substrate, and fluorinate it to form a (FeCoNiCuZn)F high entropy fluoride electrocatalyst.

[0011] The specific steps include:

[0012] Step 1, prepare precursor solution:

[0013] According to the molar ratio of metal ions, FeCl3·6H2O, CoCl2, NiCl2·6H2O, CuCl2·6H2O, and ZnCl2 were weighed, mixed, dissolved in deionized water, and stirred evenly to obtain a precursor solution;

[0014] Step 2, preparation of high entropy alloy:

[0015] (1) Using the precursor solution as the electrolyte of the electrolytic cell, controlling the pH value of the electrolyte to be 4 to 4.5, and heating it to 40 to 45° C.;

[0016] (2) In a three-electrode system, constant potential electrodeposition was performed with nickel foam as the working electrode and graphite rod as the counter electrode. The deposition potential range was -0.2±0.05 V and the deposition time was 800-900 s.

[0017] (3) After the deposition is completed, the nickel foam electrode on which the FeCoNiCuZn high entropy alloy is deposited is ultrasonically cleaned, and then allowed to stand in air to dry, thereby obtaining a FeCoNiCuZn high entropy alloy uniformly deposited on the nickel foam;

[0018] Step 3, fluorination treatment by molten salt method:

[0019] (1) according to the molar amount of fluorine in the (FeCoNiCuZn)F high entropy fluoride electrocatalyst, weighing ammonium fluoride and heating and melting it to obtain molten ammonium fluoride;

[0020] (2) The FeCoNiCuZn high entropy alloy is placed in molten ammonium fluoride for fluorination treatment to obtain the (FeCoNiCuZn)F high entropy fluoride electrocatalyst.

[0021] The preparation method of the above-mentioned (FeCoNiCuZn)F high entropy fluoride electrocatalyst, wherein:

[0022] In step 1, the metal ion molar ratio is Fe 3+ :Co 2+ :Ni 2+ :Cu 2+ :Zn 2+ =1:1:1:1:1, the total metal ion concentration in the precursor solution ranges from 0.1 to 0.5 mol / L.

[0023] In step 2(1), the process of controlling the pH value of the electrolyte to be between 4 and 4.5 is as follows: under stirring, ammonia water or 0.1 mol / L dilute hydrochloric acid is used as a pH adjuster to adjust the pH value of the electrolyte to 4 to 4.5, and the stirring rate is 200 to 300 rpm.

[0024] In step 2(2), the size of the nickel foam used is 20 mm×10 mm×1 mm. The nickel foam is ultrasonically pretreated with a 0.5 mol / L dilute HCl solution for a pretreatment time of ≤20 min to remove oxides on the surface of the nickel foam. The nickel foam is then rinsed repeatedly with deionized water and anhydrous ethanol for multiple times and allowed to stand in the air to dry for later use.

[0025] In step 2(2), the working electrode clamp and the reference electrode clamp are clamped onto the working electrode at the same time; the nickel foam substrate needs to be placed 1 to 1.5 cm below the liquid surface of the precursor solution and soaked for 30 to 60 seconds, and maintained at a distance of 2 to 2.5 cm from the graphite rod.

[0026] In step 2 (3), after the deposition time is over, the sample is immediately taken out and ultrasonically cleaned with deionized water and anhydrous ethanol multiple times to remove excess surface sediments. The ultrasonic cleaning time is preferably 5 to 10 minutes. The sample is left to dry in the air for use. The natural drying time is ≥ 24 hours.

[0027] In step 3 (1), the temperature of the constant temperature heating table is maintained at 240° C. to 250° C., the mass of ammonium fluoride is 2 to 2.5 g, and 5 FeCoNiCuZn high entropy alloys with a size of 20 mm×10 mm×1 mm can be fluorinated.

[0028] In step 3(2), the fluorination treatment time is 60 to 70 seconds, and then the sample is quickly taken out and placed in deionized water, and rinsed with deionized water for multiple times to remove surface impurities, and then left to dry in the air.

[0029] The precursor solution prepared by mixing FeCl3·6H2O, CoCl2, NiCl2·6H2O, CuCl2·6H2O and ZnCl2 in an equal molar ratio is electro-deposited on a nickel foam substrate at a constant potential to obtain a FeCoNiCuZn high entropy alloy electrocatalyst. After fluorination treatment, washing, standing and drying, a (FeCoNiCuZn)F high entropy fluoride electrocatalyst is obtained which can be directly used as a working electrode.

[0030] Compared with the prior art, the (FeCoNiCuZn)F high entropy fluoride electrocatalyst and its preparation method and application of the present invention have the following beneficial effects:

[0031] The (FeCoNiCuZn)F high entropy fluoride electrocatalysts in the present invention are composed of low-cost transition metal elements Fe, Co, Ni, Cu, and Zn. Compared with the Pt, IrO2, and RuO2 precious metal catalysts currently used commercially for electrocatalytic hydrogen evolution reaction and oxygen evolution reaction, they not only have cost advantages, but also have relatively excellent bifunctional electrocatalytic activity for hydrogen evolution reaction and oxygen evolution reaction, and have certain excellent potential in the field of water electrolysis.

[0032] The invention adopts a simple constant potential electrodeposition method combined with a molten salt method to prepare the (FeCoNiCuZn)F high entropy fluoride electrocatalyst. The preparation method is simple to operate. Under 1 mol / L KOH alkaline conditions, the hydrogen evolution reaction of the (FeCoNiCuZn)F high entropy fluoride electrocatalyst of the invention is measured at a current density of 10 mA cm -2The overpotential is 21 mV and the Tafel slope is 24.57 mV·dec -1 To avoid the oxidation peak of nickel foam interfering with the performance test during the oxygen evolution reaction, the current density of the oxygen evolution reaction was measured at 100 mA cm -2 The overpotential is 274 mV and the Tafel slope is 48.86 mV·dec -1 , and has excellent electrocatalytic performance in hydrogen evolution reaction and oxygen evolution reaction.

[0033] Within the scope of understanding, the implementation method provided by the present invention can realize the present invention and is not limited to the above examples. At the same time, the interval range of various preparation technical parameters (high entropy system components, electrolyte concentration, pH value, deposition potential, deposition time, and amount of ammonium fluoride used) can realize the present invention. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should belong to the protection scope of the claims attached to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 XRD patterns of the FeCoNiCuZn high entropy alloy and (FeCoNiCuZn)F high entropy fluoride electrocatalysts prepared in the embodiments of the present invention.

[0035] Figure 2 Comparison of high-resolution X-ray photoelectron spectra of the FeCoNiCuZn high-entropy alloy and the (FeCoNiCuZn)F high-entropy fluoride electrocatalyst prepared in the embodiments of the present invention.

[0036] Figure 3 Performance test diagrams of the FeCoNiCuZn high entropy alloy and (FeCoNiCuZn)F high entropy fluoride electrocatalyst prepared in the embodiments of the present invention; (a) hydrogen evolution reaction polarization curve; (b) oxygen evolution reaction polarization curve; (c) electrochemical impedance diagram at a potential of -1.1V; (d) electrochemical impedance diagram at a potential of 0.48V; (e) Tafel slope diagram of hydrogen evolution reaction; (f) Tafel slope diagram of oxygen evolution reaction.

[0037] Figure 4 Performance test comparison of FeCoNiCuZn high entropy alloy and (FeCoNiCuZn)F high entropy fluoride electrocatalyst prepared in the embodiment of the present invention; (a) Hydrogen evolution reaction 10mA·cm -2 Overpotential and corresponding current density at -0.075 V; (b) oxygen evolution reaction 100 mA cm -2 The overpotential and the corresponding current density at 1.53V.

[0038] Figure 5Comparison of electrocatalytic performance tests of the (FeCoNiCuZn)F high entropy fluoride electrocatalyst prepared in the embodiment of the present invention and (FeCoNiCuZn)S, (FeCoNiCuZn)N, and (FeCoNiCuZn)P prepared in the comparative examples; (a) polarization curve of hydrogen evolution reaction; (b) polarization curve of oxygen evolution reaction. DETAILED DESCRIPTION

[0039] It should be noted that the following embodiments are described in detail in conjunction with the accompanying drawings in order to better illustrate the content of the present invention, but the content of the present invention is not limited to the following embodiments. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by ordinary technicians in the technical field to which this application belongs.

[0040] Example

[0041] The invention provides a (FeCoNiCuZn)F high entropy fluoride electrocatalyst.

[0042] A method for preparing a (FeCoNiCuZn)F high entropy fluoride electrocatalyst comprises the following specific steps:

[0043] Step 1, prepare the precursor electrolyte:

[0044] (1) According to the metal ion molar ratio Fe 3+ :Co 2+ :Ni 2+ :Cu 2+ :Zn 2+ =1:1:1:1:1 Weigh the corresponding FeCl3·6H2O (2.7029 g), CoCl2 (1.298 g), NiCl2·6H2O (2.3769 g), CuCl2·6H2O (1.7048 g), and ZnCl2 (1.363 g), mix them, and dissolve them in 100 mL of deionized water. Cover the beaker containing the electrolyte with a sealing film, place it on a magnetic stirrer and stir for 3 to 4 hours until a uniformly mixed precursor solution is obtained;

[0045] Step 2, preparation of high entropy alloy:

[0046] (1) a certain volume of the mixed precursor solution obtained in step 1 is measured and placed in an electrolytic cell, which is stably clamped on a constant temperature water bath, and under stirring, ammonia water or 0.1 mol / L dilute hydrochloric acid is used as a pH adjuster, and the pH value of the electrolyte is uniformly adjusted to 4 at a stirring rate of 200 rpm, and the water bath is heated to 40° C.;

[0047] (2) Using a CHI760E electrochemical workstation, in a three-electrode system, nickel foam is used as the working electrode, and a graphite rod is used as the counter electrode. The working electrode clip and the reference electrode clip are clamped onto the working electrode at the same time, and then placed in the precursor solution. In addition, the nickel foam substrate needs to be placed 1 to 1.5 cm below the liquid surface of the precursor solution and soaked for 30 to 60 seconds, and maintained at a distance of 2 to 2.5 cm from the graphite rod. A constant potential electrodeposition method is used, with a deposition potential of -0.2 V and a deposition time of 900 seconds.

[0048] The size of the nickel foam used is 20 mm×10 mm×1 mm. The nickel foam is ultrasonically pretreated with a 0.5 mol / L dilute HCl solution for a pretreatment time of ≤20 min to remove oxides on the surface of the nickel foam, and is repeatedly rinsed with deionized water and anhydrous ethanol for multiple times, and then left to dry in the air for later use.

[0049] (3) After the deposition is completed, the nickel foam substrate loaded with the high entropy alloy is ultrasonically rinsed multiple times with deionized water and anhydrous ethanol in sequence. The ultrasonic cleaning time is 5 to 10 minutes, and the substrate is dried in air for ≥ 24 hours to obtain a FeCoNiCuZn high entropy alloy uniformly deposited on the substrate. The XRD pattern is shown in FIG. Figure 1 Its high-resolution X-ray photoelectron spectrum is shown in Figure 2 .

[0050] Step 3, fluorination treatment:

[0051] (1) Adjust the temperature of the thermostatic heating table to 250° C., weigh 2 g of ammonium fluoride into a beaker, and place the beaker on the thermostatic heating table;

[0052] (2) After the ammonium fluoride is completely melted, the FeCoNiCuZn high entropy alloy obtained in step 2 is placed in molten ammonium fluoride for 60 seconds, then quickly taken out and placed in deionized water, and rinsed with deionized water for multiple times to remove surface impurities, and then allowed to stand and dry in air to obtain a (FeCoNiCuZn)F high entropy fluoride electrocatalyst, whose XRD pattern is shown in Figure 1 Its high-resolution X-ray photoelectron spectrum is shown in Figure 2 .

[0053] The present invention provides an application of a (FeCoNiCuZn)F high entropy fluoride electrocatalyst in electrocatalytic hydrogen evolution reaction and oxygen evolution reaction under 1 mol / L KOH alkaline conditions:

[0054] The prepared (FeCoNiCuZn)F high entropy fluoride electrocatalyst was cut into a 10 mm × 10 mm working electrode, and the loading amount of the (FeCoNiCuZn)F high entropy fluoride on the nickel foam substrate was 4.8-5.2 mg cm -2, Ag / AgCl electrode was used as reference electrode, and graphite rod was used as counter electrode. The electrocatalytic performance was tested using Shanghai Chenhua electrochemical workstation CHI760E. The number of cyclic voltammetry (CV) cycles was 20 times, and the scan rate was 50 mV·s -1 The scanning rate of linear sweep voltammetry (LSV) was 5 mV·s -1 , ohm compensation is 90%. The test environment is 50℃.

[0055] from Figure 1 The XRD results show that the XRD results of the above-mentioned FeCoNiCuZn high entropy alloy and (FeCoNiCuZn)F high entropy fluoride electrocatalyst are consistent with the standard PDF card (85-1326), which is a cubic crystal system with a space group of Fm-3m (225), indicating that the (FeCoNiCuZn)F high entropy fluoride electrocatalyst is a stable face-centered cubic single-phase structure. Figure 2 The high-resolution X-ray photoelectron spectrum shows that all metal elements exist evenly, and the valence state of the Fe element shifts to a certain extent towards low binding energy after F doping. Figure 3 The performance of the hydrogen evolution reaction and oxygen evolution reaction of the FeCoNiCuZn high entropy alloy electrocatalyst and the (FeCoNiCuZn)F high entropy fluoride electrocatalyst was tested. Under the alkaline condition of 1 mol / L KOH, the hydrogen evolution reaction of the (FeCoNiCuZn)F high entropy fluoride electrocatalyst in this example was measured at a current density of 10 mA cm -2 The overpotential is 21 mV and the Tafel slope is 24.57 mV·dec -1 ; The oxygen evolution reaction is at a current density of 100 mA cm -2 The overpotential is 274 mV and the Tafel slope is 48.86 mV·dec -1 . Figure 4 The performance comparison chart shows that in the hydrogen evolution reaction, the current density of the (FeCoNiCuZn)F high entropy fluoride electrocatalyst is nearly 4 times higher than that of the FeCoNiCuZn high entropy alloy electrocatalyst at a potential of -0.075V. -2 At a current density of 1.53 V, the overpotential of the (FeCoNiCuZn)F high entropy fluoride electrocatalyst is much lower than that of the FeCoNiCuZn high entropy alloy electrocatalyst, indicating that the performance of the hydrogen evolution reaction is greatly improved after fluorination. For the oxygen evolution reaction, the current density of the (FeCoNiCuZn)F high entropy fluoride electrocatalyst is improved to a certain extent compared with the FeCoNiCuZn high entropy alloy electrocatalyst at a potential of 1.53 V. At the same time, at 100 mA cm -2At a current density of , the overpotential of the (FeCoNiCuZn)F high entropy fluoride electrocatalyst is also lower than that of the FeCoNiCuZn high entropy alloy electrocatalyst. This further shows that the (FeCoNiCuZn)F high entropy fluoride electrocatalyst has excellent bifunctional electrocatalytic performance in hydrogen evolution reaction and oxygen evolution reaction.

[0056] Example 2

[0057] The same as Example 1, except that, during the preparation of the high entropy alloy, the pH value of the electrolyte is controlled at 4.5 and heated to 42° C.; the deposition potential range is -0.25 V, and the deposition time is 850 s.

[0058] Example 3

[0059] Same as Example 1, except that the deposition potential range is -0.25 V and the deposition time is 800 s.

[0060] Example 4

[0061] The same as Example 1, except that the pH value of the electrolyte is controlled at 4.2 and heated to 45° C.; the deposition potential range is -0.21 V, and the deposition time is 820 s.

[0062] Example 5

[0063] The same as Example 1, except that the pH value of the electrolyte is controlled at 4-4.5 and heated to 40-45° C.; the deposition potential range is -0.15 V, and the deposition time is 860 s.

[0064] Comparative Example 1

[0065] Nitride (melamine) is used to replace ammonium fluoride. The difference is that the nitridation process is carried out in a tubular furnace with an argon atmosphere, and the obtained product is (FeCoNiCuZn)N high entropy nitride. Figure 5 Compared with (FeCoNiCuZn)F high entropy fluoride, (FeCoNiCuZn)N high entropy nitride has relatively poor performance in hydrogen evolution reaction and oxygen evolution reaction.

[0066] Comparative Example 2

[0067] Phosphide (sodium hypophosphite) is used to replace ammonium fluoride. The difference is that the phosphating process is carried out in an argon atmosphere tube furnace, and the obtained high entropy phosphide is (FeCoNiCuZn)P. Figure 5 Compared with the (FeCoNiCuZn)F high entropy fluoride, the (FeCoNiCuZn)P high entropy phosphide has relatively poor performance in hydrogen evolution reaction and oxygen evolution reaction.

[0068] Comparative Example 3

[0069] Sulfide (thiourea) is used to replace ammonium fluoride. The difference is that the sulfidation process is carried out in a tubular furnace with an argon atmosphere, and the obtained product is (FeCoNiCuZn)P high entropy sulfide. Figure 5 Compared with (FeCoNiCuZn)F high entropy fluoride, (FeCoNiCuZn)N high entropy nitride has relatively poor performance in hydrogen evolution reaction and oxygen evolution reaction.

[0070] Combining all the above comparative examples, for hydrogen evolution reaction performance, (FeCoNiCuZn)F>(FeCoNiCuZn)S>(FeCoNiCuZn)P>(FeCoNiCuZn)N; for oxygen evolution reaction performance, (FeCoNiCuZn)F>(FeCoNiCuZn)P>(FeCoNiCuZn)N≈(FeCoNiCuZn)S. The results show that compared with other chemical modification treatments, the (FeCoNiCuZn)F high entropy fluoride electrocatalyst obtained by fluorination treatment of FeCoNiCuZn high entropy alloy has better bifunctional electrocatalytic activity in hydrogen evolution reaction and oxygen evolution reaction.

[0071] The above description is only the preferred embodiment of the present invention, and has no limiting effect on the present invention. For those skilled in the art, the present invention may have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A (FeCoNiCuZn)F high entropy fluoride electrocatalyst, characterized in that The metal ion molar ratio in the precursor solution used is Fe 3+ :Co 2+ :Ni 2+ :Cu 2+ :Zn 2+ =1:1:1:1:1, where 10cm 3 The corresponding molar amount of the fluorine-containing compound added to the FeCoNiCuZn high entropy alloy is 0.054-0.067 mol; The fluorine-containing compound is ammonium fluoride; The (FeCoNiCuZn)F high entropy fluoride electrocatalyst has a cubic crystal structure and a Fm-3m space group; Under 1 mol / L KOH alkaline conditions, the hydrogen evolution reaction of (FeCoNiCuZn)F high entropy fluoride electrocatalyst was measured at a current density of 10 mA cm -2 The overpotential is 21 mV and the Tafel slope is 24.57 mV·dec -1 ; The current density of oxygen evolution reaction was measured at 100 mA cm -2 The overpotential is 274 mV and the Tafel slope is 48.86 mV·dec -1 .

2. A method for preparing a (FeCoNiCuZn)F high entropy fluoride electrocatalyst, characterized in that: The metal ion molar ratio Fe 3+ :Co 2+ :Ni 2+ :Cu 2+ :Zn 2+ =1:1:1:1:1 prepare a precursor solution, perform electrodeposition, form a FeCoNiCuZn high entropy alloy on a porous conductive nickel foam substrate, and fluorinate the alloy to form a (FeCoNiCuZn)F high entropy fluoride electrocatalyst; comprising the following steps: Step 1, prepare precursor solution: According to the molar ratio of metal ions, FeCl3·6H2O, CoCl2, NiCl2·6H2O, CuCl2·6H2O, and ZnCl2 were weighed, mixed, dissolved in deionized water, and stirred evenly to obtain a precursor solution; Step 2, preparation of high entropy alloy: (1) Using the precursor solution as the electrolyte of the electrolytic cell, controlling the pH value of the electrolyte to be 4 to 4.5, and heating it to 40 to 45° C.; (2) In a three-electrode system, constant potential electrodeposition was performed with nickel foam as the working electrode and graphite rod as the counter electrode. The deposition potential range was -0.2±0.05 V and the deposition time was 800-900 s. (3) After the deposition is completed, the nickel foam electrode on which the FeCoNiCuZn high entropy alloy is deposited is ultrasonically cleaned, and then allowed to stand in air to dry, thereby obtaining a FeCoNiCuZn high entropy alloy uniformly deposited on the nickel foam; Step 3, fluorination treatment by molten salt method: (1) according to the molar amount of fluorine in the (FeCoNiCuZn)F high entropy fluoride electrocatalyst, weighing ammonium fluoride and heating and melting it to obtain molten ammonium fluoride; (2) The FeCoNiCuZn high entropy alloy is placed in molten ammonium fluoride for fluorination treatment to obtain the (FeCoNiCuZn)F high entropy fluoride electrocatalyst.

3. The method for preparing the (FeCoNiCuZn)F high entropy fluoride electrocatalyst according to claim 2, characterized in that: In step 1, the total metal ion concentration in the precursor solution is in the range of 0.1 to 0.5 mol / L.

4. The method for preparing the (FeCoNiCuZn)F high entropy fluoride electrocatalyst according to claim 2, characterized in that: In step 2(1), the process of controlling the pH value of the electrolyte to be between 4 and 4.5 is as follows: under stirring, ammonia water or 0.1 mol / L dilute hydrochloric acid is used as a pH adjuster to adjust the pH value of the electrolyte to 4 to 4.5, and the stirring rate is 200 to 300 rpm.

5. The method for preparing the (FeCoNiCuZn)F high entropy fluoride electrocatalyst according to claim 2, characterized in that: In step 2(2), the working electrode clamp and the reference electrode clamp are clamped onto the working electrode at the same time; the nickel foam substrate needs to be placed 1 to 1.5 cm below the liquid surface of the precursor solution and soaked for 30 to 60 seconds, and maintained at a distance of 2 to 2.5 cm from the graphite rod.

6. The method for preparing the (FeCoNiCuZn)F high entropy fluoride electrocatalyst according to claim 2, characterized in that: In step 3 (1), the heating melting temperature is maintained at 240° C. to 250° C., and 2 to 2.5 g of ammonium fluoride can be used to fluorinate 5 FeCoNiCuZn high entropy alloys with a size of 20 mm×10 mm×1 mm.

Citation Information

Patent Citations

  • Preparation and application of FeCoNiCuMn nano high-entropy alloy electrocatalyst

    CN115142073A